Analysis and Design of UI/UX Mobile Applications for Marketing of UMKM Products Using Design Thinking Method - Dewi, Eva Zuliana; Fransisca, May; Handayani, Rani Irma; Cahyanti, F. Lia Dwi (Politeknik Ganesha Medan, 2022)
The “Product UMKM Online” website is a marketplace or e-commerce that is used as a medium to facilitate UMKM actors in Indonesia in marketing their products and helping UMKM actors to further increase their product sales and help play an important role in the UMKM business process in Indonesia. however, the author found on the website there are still some shortcomings, so the author researched. this study aims to provide recommendations as reference material in the form of a prototype design so that it can be developed in the future. in this study, the author uses a Design Thinking method approach to be able to produce a UI/UX design that fits the user’s needs. There are several processes in the research method that the author uses, namely empathize, define, ideate, prototype, and test. The prototype stage goes through several stages, namely understanding a problem, designing a solution than making a prototype which is then tested on several users. The application of the Design Thinking method in this research is expected to improve the user’s experience better than before.